Microbiomes of stony and soft deep-sea corals share rare core bacteria - Christina A. Kellogg (Microbiome, 2019)
Abstract Background Numerous studies have shown that bacteria form stable associations with host corals and have focused on identifying conserved “core microbiomes” of bacterial associates inferred to be serving key roles in the coral holobiont. Because studies tend to focus on only stony corals (order Scleractinia) or soft corals (order Alcyonacea), it is currently unknown if there are conserved bacteria that are shared by both. A meta-analysis was done of 16S rRNA amplicon data from multiple studies generated via identical methodology to allow direct comparisons of bacterial associates across seven deep-sea corals, including both stony and soft species: Anthothela grandiflora, Anthothela sp., Lateothela grandiflora, Lophelia pertusa, Paramuricea placomus, Primnoa pacifica, and Primnoa resedaeformis. Results Twenty-three operational taxonomic units (OTUs) were consistently present in greater than 50% of the coral samples. Seven amplicon sequence variants (ASVs), five of which corresponded to a conserved OTU, were consistently present in greater than 30% of the coral samples including five or greater coral species. A majority of the conserved sequences had close matches with previously identified coral-associated bacteria. While known to dominate tropical and temperate coral microbiomes, Endozoicomonas were extremely rare or absent from these deep-sea corals. An Endozoicomonas OTU associated with Lo. pertusa in this study was most similar to those from shallow-water stony corals, while an OTU associated with Anthothela spp. was most similar to those from shallow-water gorgonians. Conclusions Bacterial sequences have been identified that are conserved at the level of class Anthozoa (i.e., found in both stony and soft corals, shallow and deep). These bacterial associates are therefore hypothesized to play important symbiotic roles and are highlighted for targeted future study. These conserved bacterial associates include taxa with the potential for nitrogen and sulfur cycling, detoxification, and hydrocarbon degradation. There is also some overlap with kit contaminants that need to be resolved. Rarely detected Endozoicomonas sequences are partitioned by whether the host is a stony coral or a soft coral, and the finer clustering pattern reflects the hosts’ phylogeny.